Unipampa: primeiros passos no avanço da educação a distância - (:unkn) unknown (Universidade Federal do Pampa, 2018)
This paper present Unipampa advances in education, especially in the distance mode, through actions that meet the development of the region and the country. An action that undoubtedly expands the offer of vacancies in higher education through undergraduate and postgraduate courses, further reinforcing government policies for access to the public university. The methodology for choosing the episodes followed the chronological order of actions since the first group established and the reflection of this work in the sectors and documents of the Institution towards the consolidation of the distance modality.
Keywords: Políticas públicas; Unipampa; Educação a distância; Governamental policies; Distance education; Unipampa; CNPQ::CIENCIAS SOCIAIS APLICADAS